2020
DOI: 10.1007/s12028-020-00994-4
|View full text |Cite
|
Sign up to set email alerts
|

Contusion Progression Following Traumatic Brain Injury: A Review of Clinical and Radiological Predictors, and Influence on Outcome

Abstract: Secondary injuries remain an important cause of the morbidity and mortality associated with traumatic brain injury (TBI). Progression of cerebral contusions occurs in up to 75% of patients with TBI, and this contributes to subsequent clinical deterioration and requirement for surgical intervention. Despite this, the role of early clinical and radiological factors in predicting contusion progression remains relatively poorly defined due to studies investigating progression of all types of hemorrhagic injuries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 65 publications
10
62
0
Order By: Relevance
“…The current study came in accordance with a research which was conducted by Adatia et al (16) and demonstrated that, progression of cerebral contusions occurs in up to 75% of patients with TBI whatever the age and this contributes to subsequent clinical deterioration and requirement for surgical intervention. On the contrary, Ushewokunze et al (17) demonstrated that, acute subdural hematoma was the commonest pathology for elderly TBI, which corresponds with a coroner's report that subdural hematoma was the commonest lesion of the deceased elderly persons with head injuries (18) .…”
Section: Discussionsupporting
confidence: 91%
“…The current study came in accordance with a research which was conducted by Adatia et al (16) and demonstrated that, progression of cerebral contusions occurs in up to 75% of patients with TBI whatever the age and this contributes to subsequent clinical deterioration and requirement for surgical intervention. On the contrary, Ushewokunze et al (17) demonstrated that, acute subdural hematoma was the commonest pathology for elderly TBI, which corresponds with a coroner's report that subdural hematoma was the commonest lesion of the deceased elderly persons with head injuries (18) .…”
Section: Discussionsupporting
confidence: 91%
“…Our study found that sustaining a contusion was associated with lower odds for mortality (OR = 0.09, P = 0.015). These findings agree with a study by Adatia, Newcombe & Menon (2020) , in which mortality due to brain contusions has been linked to the ability to predict their clinical or radiological deterioration before progression. Using lessons learned from a study on determinants of outcome of extra-axial hematoma ( Ssebakumba et al, 2020 ), it was possible for the attending clinicians in this study to predict which patients with contusions would deteriorate by risk stratification based on their smoking status, admission GCS, systolic BP, initial contusion size and location and co-existence of extra-axial hematoma and cerebral edema on brain CT image, to discern who needed an emergency decompressive craniectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, there is ample opportunity to intervene if proper treatment can be identi ed. While much is known about predictors of hemorrhage progression following TBI [2], surprisingly little has been written about the temporal progression of these lesions. Fundamental questions therefore remain unanswered, such as: When do traumatic intracranial lesions stop progressing?…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Several well-written studies have provided some answers. Among the various subtypes of intracranial bleeds, contusions seem to be the most likely to progress, and in the majority of cases this occurs within the rst 24 hours after injury [2]. However, limitations to these studies have restricted their clinical applicability.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation